Numerical Method for Fractional Model of Newell-Whitehead-Segel Equation - Prakash, Amit; Verma, Vijay (Frontiers in Physics, 2019)
The aim of the present work is to devote a friendly approach based on Adomian decoposition method (ADM) to find the numerical solution of the time-fractional Newell-Whitehead-Segel equation. Newell-Whitehead-Segel equation plays an efficient role in nonlinear systems which describe the appearance of the stripe patterns in two dimensional systems. The numerical results obtained by proposed method are compared with exact solution for different values of fractional order α. Plotted graph illustrate the efficiency and accuracy of the proposed technique.